Implementasi Regulasi BUM Desa: Studi Perbandingan antara UU Cipta Kerja dan Peraturan Daerah Kabupaten Wonogiri - Wahyuni, Sri; Diartika, Firda; Mazaya, Amalia Febryane Adhani (CV. Kurnia Grup, 2025)
Village-Owned Enterprises (BUM Desa) play a strategic role in improving the welfare of village communities through independent and sustainable management of local potential. The urgency of this research lies in the importance of understanding the implications of regulatory changes on the existence and management of BUM Desa, considering that BUM Desa is defined in Law Number 6 of 2014 as a business entity whose capital is wholly or mostly owned by the village through direct participation originating from village assets separated to manage village assets and potential. This study aims to compare the Job Creation Law with Government Regulations and Regional Regulations on BUM Desa. This study uses a qualitative descriptive approach with a literature study method. The analysis results show that there are twelve main discussion scopes that are compared, including provisions in the Job Creation Law, Government Regulation Number 11 of 2021 concerning BUM Desa, and Wonogiri Regency Regional Regulation Number 6 of 2016. This comparison shows differences and adjustments to legal norms that impact the legal status, institutions, and governance of BUM Desa at the regional level, so that adjustments to regulations at the regional level regarding BUM Desa provisions are needed in accordance with national regulatory developments.